‫‫أثر‬‫صيغ‬ ‫التمويل‬ ‫في‬ ‫الأجل‬ ‫القصير‬ ‫على‬ ‫كفاءة‬ ‫إدارة‬ ‫مؤشرات‬ ‫مكونات‬ ‫الإحتياج ‬‫للمال‬ ‫المتداول‬ ‫دراسة ‬‫حالة‬ ‫مطاحن‬ ‫بلغيث‬ ‫الكبرى‬ ‬ ‫‬ - زينب ‫زعلاني‬‫ ‬; أحالم ‫ملاوحية‬‫‬ (My University, 2018)
The aim of the study is to show the effect of short term financing formulas on the adequacy of indicators of the components of the need for economic institutions, as these variables are effective elements in the process of the institution's activity In order to deal with the problem of the subject and to test hypotheses, the Bellgith mills were selected as a sample for the study during the period (2010-2017) based on the program .Eviews 8 The study concluded that there is a real relationship between the indicators of growth of the need, the index of suppliers to the intermediate consumption, the effect of these ratios on the index of stocks to intermediate consumption ,and there was no effect of liquidity ratios On .indicators of need. One of the recommendations is to improve the status of the financial indicators of the institution and to increase the negotiation of the with its suppliers and customers in order to improve the efficiency of indicators of need. ................................................... هدفت الدراسة إلى بيان أثر صيغ التمويل قصير الأجل على مدى كفاية مؤشرات مكونات الحاجة إلى المؤسسات الاقتصادية، مثل هذه تعتبر المتغيرات عناصر فعالة في عملية نشاط المؤسسة ومن أجل معالجة مشكلة الموضوع واختبار الفرضيات، قامت مطاحن بيلجيث وتم اختيارهم كعينة للدراسة خلال الفترة (2010-2017) على أساس البرنامج .المشاهدات 8 وتوصلت الدراسة إلى وجود علاقة حقيقية بين مؤشرات النمو الحاجة، مؤشر الموردين للاستهلاك الوسيط، تأثير هذه النسب على مؤشر الأسهم للاستهلاك الوسيط، ولم يكن هناك تأثير لنسب السيولة على .مؤشرات الحاجة. ومن التوصيات تحسين وضع المؤشرات المالية للبنك المؤسسة وزيادة التفاوض مع مورديها وعملائها من أجل تحسين كفاءة مؤشرات الحاجة.